Mapping Vulnerability to Climate Change in Malawi: Spatial and Social Differentiation in the Shire River Basin - Coulibaly, Jeanne Y.; Mbow, Cheikh; Sileshi, Gudeta W.; Beedy, Tracy; Kundhlande, Godfrey; Musau, John (American Journal of Climate Change, 2015)
This article analyses vulnerability to climate related shocks across five districts in the shire river basin of Malawi.The analysis employs an indicator approach that integrates biophysical and socio-economic indices.Principal component statistical analysis was used to calculate an index for adaptive capacity, sensitivity and exposure to climate impact for each of the five districts.These indices were aggregated to develop a vulnerability index differentiated also by gender for the surveyed districts.The results showed that Chikwawa, Machinga and Blantyre appear to be more vulnerable to climate related shocks compared with Mwanza and Zomba.Women in Chikwawa are also found to be the most susceptible to the climate hazards impacts.To reduce vulnerability to climate impact, the study suggests that the national adaptation strategies adopted by the government should be mainstreamed into specific local adaptation actions that can be accessible and adopted by the community.Specific emphasis should be given to the improvement of women's welfare through better access to productive assets and resources.
openalex: W1744774458 mag: 1744774458
Keywords: openalex:import